Agrifood systems policy research: historical evolution of agrifood systems in Nepal - Sugden, Fraser; Dhakal, S.; Rai, J. (CGIAR Initiative on Transforming Agrifood Systems in South Asia, 2022)
This report explores the agrarian history of Nepal over the last 500 years, and the historical, social, and political trajectories that still shape modern agrifood systems in Nepal. The report is organised according to the main epochs in Nepal’s political-economic history. The study explores the complex layers of factors which vary across space according to contemporary and historic state formations, the local agroecology and indigenous and imported cultural-economic institutions and technologies that shape regional diversity in modes of production and food production systems across Nepal. The study is based on readily available documents including secondary literature and archival data as data sources.